Peer-to-peer based distributed file systems. (9th February 2007) - Vincze, Gabor; Pap, Zoltan; Horvath, Robert
In this paper, we present the problem of building a file system on top of a peer-to-peer network. While peer-to-peer networks are offering an increasing number of services, the scale of network file systems is increasing to that of distributed storage systems spanning the globe. The convergence of the two fields should give birth to decentralised, distributed and self-configuring storage networks. We show here the evolution of peer-to-peer networks and network file systems, and the difficulties that have prevented offering file system type services in peer-to-peer networks so far. We present CFS and Ivy, two DHT-based file systems that fail, however, to solve key problems, and outline possible solutions in the future.